2014
DOI: 10.1007/s12070-014-0791-6
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Intranasal Splints After Partial Inferior Turbinectomy

Abstract: To assess the value of using the intranasal septal splint after partial inferior turbinectomy (PIT) surgery. Prospective, randomized comparative study. The study was conducted over a period of 2 years from January 2012 to January 2014 at Minia University hospital, Minia, Egypt. A total of 100 patients underwent bilateral PIT. They were randomly divided into 2 groups. Group A included 50 patients had PIT with intranasal splints and group B included 50 patients had PIT without splints. A comparison was made betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…[19] It has also been shown that in the short-term follow-up, increased postoperative pain may result in a considerable reduction in the rate of intranasal adhesion. [20] In current study nasal adhesion was found in 9 (7.5%) and rest were 111 (92.5%) patients did not have nasal adhesion. Intranasal splints used in septal surgery have been demonstrated to dramatically minimise the production of postoperative nasal adhesions by 2.5 percent when compared to basic nasal packing, according to Veluswamy et al2012 .…”
Section: Nasal Adhesionmentioning
confidence: 46%
“…[19] It has also been shown that in the short-term follow-up, increased postoperative pain may result in a considerable reduction in the rate of intranasal adhesion. [20] In current study nasal adhesion was found in 9 (7.5%) and rest were 111 (92.5%) patients did not have nasal adhesion. Intranasal splints used in septal surgery have been demonstrated to dramatically minimise the production of postoperative nasal adhesions by 2.5 percent when compared to basic nasal packing, according to Veluswamy et al2012 .…”
Section: Nasal Adhesionmentioning
confidence: 46%
“…The resection involved the mucosa and a part of the inferior turbinate bone (depending on the degree of hypertrophy). The study indicated that the use of nasal separators after partial resections of the inferior turbinates statistically significantly reduces the incidence of intranasal adhesions [6].…”
Section: Resultsmentioning
confidence: 91%
“…The use of intra-anasal splints in the one-wall technique also demonstrated that increments in postoperative pain may lead to significantly reduced rates of intranasal adhesion in the short-term follow-up. 26 In three-month postoperative follow-ups, von Schoenberg and Robinson 27 observed that the split and non-split groups had the same low 2% adhesion rate that was shown in the early ambulatory check-up with 8 meticulous nasal baths weekly. Cook et al 28 revealed an insufficient intranasal split to avoid intranasal attachment (6.5% split versus 7.0% non-split) and concluded that intranasal splitting is not clearly advantageous, thus it should be done sparingly and advised for nasal toilets after septal surgery 9.…”
Section: Discussionmentioning
confidence: 88%